1985
DOI: 10.1111/j.1528-1157.1985.tb05698.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Valproate on Sleep, Reaction Times, and Visual Evoked Potential in Normal Subjects

Abstract: The effect of enteric-coated sodium valproate on 10 normal volunteer subjects was evaluated using simple reaction times, the visual evoked potential (VEP), and EEG sleep recording. Placebo, low-drug (500 mg), high-drug (1,000 mg), and withdrawal conditions were investigated. No significant treatment effect was found for simple reaction time nor was there any significant effect on either the latency or the amplitude of the VEP. Sleep recordings were analysed visually and also using an automated technique consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 5 publications
1
29
1
2
Order By: Relevance
“…Evoked potentials have been used in the assessment of the effects of AEDs on central neural conduction [4,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Evoked potentials have been used in the assessment of the effects of AEDs on central neural conduction [4,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Harding et al [13] found no effects of VPA on visual EPs. The only study on the effects of VPA on BAEP, by Mervaala et al [10], demonstrated only minor effects on BAEP, consisting of a prolongation of wave V. In our study the modifications induced by VPA were similar to the modifications induced by CBZ.…”
Section: Discussionmentioning
confidence: 99%
“…In general these agents tend to increase total sleep time, decrease number of awakenings, increase NREM stages 1 and 2, and decrease NREM stages 3 and 4 and REM (15). Furthermore, sleep architectural data on these agents' use in patients with epilepsy are scarce.…”
Section: Benzodiazepines (Bdzs)mentioning
confidence: 97%